2020
DOI: 10.26452/ijrps.v11i1.1793
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a multicomponent exercise program on cognitive function and functional ability in community dwelling older adults

Abstract: Normal aging results in alterations in the structure and function of the brain, causing impairment in cognitive function and dependency in performing activities of daily living. A multicomponent physical activity program has been recommended to maintain physical and cognitive function in elderly individuals. The present study aimed at measuring the effect of such an exercise program on the cognitive function and activities of daily living(ADL) function in community dwelling elderly individuals. 52 elderly adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…On the other hand, the experimental group showed a statistically significant improvement in all the dimensions of the MMSE, except in calculation and language (Table 3); however, when compared to the control group, significant differences were found between the two groups in the five dimensions and the opposite behaviour of these variables in the two groups (Table 5 and Figure 3). Although some authors have reported that the effect of exercise does not improve the cognitive level in all dimensions [63,68], the scientific literature shows a large amount of recent evidence on the improvement of the cognitive state in older adults after carrying out different types of physical exercise programs [69][70][71]. Thus, specifically older adults with type 2 diabetes, undergoing structured physical training, have shown improvements in aspects of cognitive function such as concentration and attention [72].…”
Section: Cognitive Statementioning
confidence: 99%
“…On the other hand, the experimental group showed a statistically significant improvement in all the dimensions of the MMSE, except in calculation and language (Table 3); however, when compared to the control group, significant differences were found between the two groups in the five dimensions and the opposite behaviour of these variables in the two groups (Table 5 and Figure 3). Although some authors have reported that the effect of exercise does not improve the cognitive level in all dimensions [63,68], the scientific literature shows a large amount of recent evidence on the improvement of the cognitive state in older adults after carrying out different types of physical exercise programs [69][70][71]. Thus, specifically older adults with type 2 diabetes, undergoing structured physical training, have shown improvements in aspects of cognitive function such as concentration and attention [72].…”
Section: Cognitive Statementioning
confidence: 99%
“…The World Health Organization promotes the active aging through the practice of physical activities by a minimum of 30 minutes per day [63], which is due to organize in a program of physical exercise according to the functional capacity of the elderly adults, specifying the type of exercise, intensity, volume and frequency [64], besides to orient on the structure that must have the session of exercises and use materials readily accessible in the home. In attention to these recommendations it is considered pertinent to use multicomponent programs by its positive impact in the functionality and the improvement of the physical capacities of aerobic resistance, force, balance, agility and amplitude to articulate, besides to contain activities that stimulate the cognitive functions and help to improve the mental health [65][66][67]. Proceeding, we will summarize the recommendations to prescribe physical activities in the home for elderly adults:…”
Section: Strategies For Promoting Maintain or Improve Elderly Adults Healthmentioning
confidence: 99%
“…Growing scientific evidence suggests that different interventions and exercise modalities have benefits on the health and well-being of older adults, improving physical capacities, metabolic variables, depression, anxiety as well as cognitive function, both in normal states of brain aging and in different stages of cognitive impairment [12][13][14][15][16][17][18][19][20][21]. In particular, it has been suggested that although routine exercise generates physiological brain adaptations, when instructional methods challenge the ability to think and promote different movements, cognitive function is improved and maintained more efficiently [22]; this is typical of interventions based on dance and choreographic activities involving balance and coordination, which have been associated with positive effects on cognition [23], specifically by improving functional connectivity, cognitive performance and increasing brain volumes in the elderly [24].…”
Section: Introductionmentioning
confidence: 99%